(untitled) (International Journal of Environmental Sciences, 2025)
Plastic waste in municipalities is a persistent environmental issue due to its poor biodegradability and diverse composition, and requires innovative approaches to sustainable valorization. This would be doubly beneficial, as such waste can be converted to syngas, providing both energy and reducing pollution. However, conventional thermal processes often exhibit poor gas yields, high tar content, and inadequate selectivity. This study aims to address the above limitations by developing a two-stage catalytic thermochemical process utilizing a Ni-Mo/CeO2 catalyst to enhance the production of syngas from municipal plastic waste. The process used is the initial pyrolysis of mixed plastic waste, catalytic steam reforming at high pressures (25bar) and high temperatures (250 °C, 275 °C, and 300 °C). Ni-Mo/CeO2 catalyst also enhanced the syngas yield significantly where H2 content was raised to 54.7 vol% H2 and 28.5 vol% CO with H2 /CO of 1.92 at optimized conditions. The gas yield was maximized to 85.6%, and char and condensate were minimized. The increased redox and dispersion properties of the catalyst, as well as the suppression of coke, were cited as the reasons behind its performance. These results demonstrate a practical route towards the circular use of non-recyclable plastics. The paper highlights the potential of the catalyst for industrial-scale use.